1989
DOI: 10.1007/bf02211841
|View full text |Cite
|
Sign up to set email alerts
|

Austism diagnostic observation schedule: A standardized observation of communicative and social behavior

Abstract: The Autism Diagnostic Observation Schedule (ADOS), a standardized protocol for observation of social and communicative behavior associated with autism, is described. The instrument consists of a series of structured and semistructured presses for interaction, accompanied by coding of specific target behaviors associated with particular tasks and by general ratings of the quality of behaviors. Interrater reliability for five raters exceeded weighted kappas of .55 for each item and each pair of raters for matche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
1,113
0
22

Year Published

1995
1995
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,806 publications
(1,143 citation statements)
references
References 23 publications
8
1,113
0
22
Order By: Relevance
“…Similar to some studies which have described a sex difference in cognitive ability with a male advantage on the spatial domains, 34 our study confirmed slight, but not significant, higher scoring of males on block-design test. It is known that better performance on block-design test is associated with autistic spectrum disorder [35][36][37] and DMD is recognized as one of susceptibility genes for autism disorder. 38,39 Suppression of the global configuration to process the information in a detailed manner, essential for this test, is described as a main characteristic of autistic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to some studies which have described a sex difference in cognitive ability with a male advantage on the spatial domains, 34 our study confirmed slight, but not significant, higher scoring of males on block-design test. It is known that better performance on block-design test is associated with autistic spectrum disorder [35][36][37] and DMD is recognized as one of susceptibility genes for autism disorder. 38,39 Suppression of the global configuration to process the information in a detailed manner, essential for this test, is described as a main characteristic of autistic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with ASD were diagnosed by experienced clinicians and a review of available medical records and/or assessment with the Autism Diagnostic Observation Schedule (ADOS; Lord, et al, 1989) confirmed that all met DSM-IV (American Psychiatric Association, 2000) criteria for Autism Spectrum Disorder. Typical participants were recruited from the local community, and individually matched to within 7 points of verbal IQ (WAIS-III UK ; The Psychological Corporation, 2000) to ASD participants.…”
Section: Participantsmentioning
confidence: 99%
“…Individuals with ASD were diagnosed by experienced clinicians and a review of available records and/or assessment with the Autism Diagnostic Observation Schedule (ADOS; Lord, et al, 1989) confirmed that all met DSM-IV (American Psychiatric Association, 2000) criteria for Autism Spectrum Disorder.…”
Section: Participantsmentioning
confidence: 99%